Counteracting the Risks of International Investment in the Conditions of War - Vasyechko, O. O. (Statistics of Ukraine, 2023)
The study aims to determine critical components of the protection of foreign investors in time of war by case of Ukraine and with account to various categories of investors. Foreign direct investment (FDI) is very volatile due to the sensitivity of foreign investors to information signals, caused by much higher riskiness of foreign markets than internal ones. Heavy FDI inflows in the past are not a guarantee of their similar inwards in the future and vice versa. The process of taking investment decisions depends on the investors’ aversion and the investment climate in a host country. The aversion of companies is dependent on size, organization and origin, which is a result of varying capabilities of counteracting international risks. The investment climate is conditional on the performance of democratic institutions, the formation of democratic society and the progress in a host country, especially in information technologies. The sensitivity to information signals essentially increases for investment projects in countries at war. The war risks feature much higher uncertainty than the risks of peacetime, being extreme by nature, which means that they may have devastating effects for an investor in spite of a low probability of the occurrence, i. e. cause abnormal losses, partial or total ruining of invested assets, or physical injuries, captivity, hostage-taking or death of company staff. This offers an argument for reasonability of the systemic approach to setting up the public policy on attracting foreign direct investment in time of war with accounting for various investor categories and special emphasis on the risk management tools that are capable to increase the level of investors’ protection and certainty. We believe that the key ones are information support for the process of taking investment decisions, formation of reserve capital by estimating value at risk and conditional value at risk, double diversification of invested assets, risk premium and international insurance of FDI. International insurance is the core component of a scheme for the protection of investors in time of war, and when the aggressor is a country with permanent membership in the UN Security Council, its guarantee will require initiatives collaborated with international partners